2023
DOI: 10.1002/jper.23-0112
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal ligament‐associated protein‐1 promotes osteoclastogenesis in mice by modulating TGF‐β1/Smad1 pathway

Abstract: BackgroundPeriodontal ligament‐associated protein‐1 (PLAP‐1), an important target molecule of osteoarthritis research, may affect alveolar bone resorption. The aim of our study was to detect the effect of PLAP‐1 comprehensively and systematically on alveolar bone resorption and the underlying mechanism in PLAP‐1‐knockout mouse models.MethodsWe used a PLAP‐1‐knockout (C57BL/6N‐Plap‐1−/−) mouse model to investigate the effect of PLAP‐1 on osteoclast differentiation and the underlying mechanism by adding Porphyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…59 Knocking down Periodontal ligamentassociated protein-1 has been shown to hinder osteoclast development and decrease alveolar bone resorption via the TGF-β1/ Smad1 signalling pathway. 62 This results suggest that high TGF-β1 may be a protective factor for periodontitis, given that it accelerates connective tissue remodelling and cell differentiation. Various investigations across different organs have demonstrated a direct relationship between activated autophagy and MFb development in tissue regeneration.…”
Section: Autophagy and Periodontal Dise A Sementioning
confidence: 81%
See 1 more Smart Citation
“…59 Knocking down Periodontal ligamentassociated protein-1 has been shown to hinder osteoclast development and decrease alveolar bone resorption via the TGF-β1/ Smad1 signalling pathway. 62 This results suggest that high TGF-β1 may be a protective factor for periodontitis, given that it accelerates connective tissue remodelling and cell differentiation. Various investigations across different organs have demonstrated a direct relationship between activated autophagy and MFb development in tissue regeneration.…”
Section: Autophagy and Periodontal Dise A Sementioning
confidence: 81%
“…In a study, TGF‐ β1 levels were found to be high in patients with chronic periodontitis 59 . Knocking down Periodontal ligament‐associated protein‐1 has been shown to hinder osteoclast development and decrease alveolar bone resorption via the TGF‐β1/Smad1 signalling pathway 62 . This results suggest that high TGF‐β1 may be a protective factor for periodontitis, given that it accelerates connective tissue remodelling and cell differentiation.…”
Section: Autophagy and Periodontal Diseasementioning
confidence: 98%